Inverted Hysteresis Loops in the Fe73.5Cu1Nb3Si13.5B9 Alloy With Small Coercivity - Shen, P. P.; Wang, Y. T.; Sun, B. A. (Frontiers in Materials, 2021)
The phenomenon of inverted hysteresis loop has been observed in many materials for the past decades. However, the physical origin of the inverted hysteresis loop has long been debated. Here, we report the completely inverted hysteresis loop with a clockwise cycle in the soft-magnetic nanocrystalline Fe73.5Cu1Nb3Si13.5B9 alloy and amorphous Fe73.5Cu1Nb3Si13.5B9 alloy at room temperature. The negative remanence and positive coercivity were observed in the descending branch of magnetization curve when the scan field range was above 1 KOe. By comparing the results with that of the standard Pd sample, we found that the net coercivities of nanocrystalline Fe73.5Cu1Nb3Si13.5B9 alloy and standard Pd sample are almost equal for the different scanning field ranges. Therefore, It is confirmed that the phenomenon of completely inverted hysteresis loop is caused by the remanence of superconducting magnet rather than the structural inhomogeneity effects. Our results suggest that special care should be taken during the measurement of hysteresis loops using MPMS 3, especially for the materials with small coercivity.